An aspirin a day? Clinical utility of aspirin therapy for the primary prevention of cardiovascular disease. (3rd August 2019) - Plazak, Michael E.; Mouradjian, Mallory T.; Watson, Kristin; Reed, Brent N.; Noel, Zachary R.; Devabhakthuni, Sandeep; Gale, Stormi E.
ABSTRACT: Introduction : Cardiovascular disease remains a leading cause of morbidity and mortality. Since the description of its therapeutic potential, aspirin has been a cornerstone of therapy following vascular events. However, aspirin in the primary prevention setting is controversial and major guideline groups provide inconsistent recommendations. Thus, there is variability in practice as providers are faced with a balance of therapeutic benefit and drug-induced harm. Areas covered : This article provides a critical appraisal of both past and present data for aspirin in the primary prevention setting. PubMed and Cochrane Central Register databases were searched from inception to May 1 st, 2019. Expert opinion : The decision to initiate or withdraw aspirin for primary prevention requires an understanding of the equilibrium between efficacy and safety. In adults greater than 70 years of age, low to moderate cardiovascular risk, controlled diabetes, or at high risk of bleeding, initiation of aspirin for primary prevention should generally be avoided. Instead, risk factor modification should be prioritized. The net benefit of aspirin in those at high risk for cardiovascular disease and in those with uncontrolled diabetes is largely unknown. Ultimately, initiation or withdrawal of aspirin therapy must involve discussion of the patient's wishes and treatment expectations.